Design Patterns for Self-Adaptive RTE Systems Specification - Mouna Ben Said; Yessine Hadj Kacem; Mickaël Kerboeuf; Nader Ben Amor; Mohamed Abid (International Journal of Reconfigurable Computing)
The development of self-adaptive real-time embedded (RTE) systems is an increasingly hard task due to the growing complexity of both hardware and software and the high variability of the execution environment. Different approaches, platforms, and middleware have been proposed in the field, from low to high abstraction level. However, there is still a lack of generic and reusable designs for self-adaptive RTE systems that fit different system domains, lighten designers’ task, and decrease development cost. In this paper, we propose five design patterns for self-adaptive RTE systems modeling resulting from the generalization of relevant existing adaptation-related works. Combined together, the patterns form the design of an adaptation loop composed of five adaptation modules. The proposed solution offers a modular, reusable, and flexible specification of these modules and enables the separation of concerns. It also permits dealing with concurrency, real-time features, and adaptation cost relative to the adaptation activities. To validate our solution, we applied it to a complex case study, a cross-layer self-adaptive object tracking system, to show patterns utilization and prove the solution benefits.